Unity Assumption in Audiovisual Emotion Perception - Sou, Ka Lon; Say, Ashley; Xu, Hong (Frontiers in Neuroscience, 2022)
We experience various sensory stimuli every day. How does this integration occur? What are the inherent mechanisms in this integration? The “unity assumption” proposes a perceiver’s belief of unity in individual unisensory information to modulate the degree of multisensory integration. However, this has yet to be verified or quantified in the context of semantic emotion integration. In the present study, we investigate the ability of subjects to judge the intensities and degrees of similarity in faces and voices of two emotions (angry and happy). We found more similar stimulus intensities to be associated with stronger likelihoods of the face and voice being integrated. More interestingly, multisensory integration in emotion perception was observed to follow a Gaussian distribution as a function of the emotion intensity difference between the face and voice — the optimal cut-off at about 2.50 points difference on a 7-point Likert scale. This provides a quantitative estimation of the multisensory integration function in audiovisual semantic emotion perception. Moreover, to investigate the variation of multisensory integration across the population, we examined the effects of several personality and autistic traits of participants. Here, we found no correlation of autistic traits with unisensory processing in a nonclinical population. Therefore, we provide a quantitative estimation of the audiovisual semantic emotion multisensory integration function with regards to stimulus intensity. Our findings shed light on the current understanding of mechanisms of multisensory integration in the population.